Hubungan Konsumsi Serat Harian Dengan Kadar Gula Darah Sewaktu Pada Pasien Diabetes Melitus Tipe 2 Tanpa Komplikasi Di Kecamatan Banda Sakti Kota Lhokseumawe - Afiqah Divaulhaq; Cut Sidrah Nadira; Noviana Zara (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia resulting from impaired insulin secretion, insulin action, or both. Indonesia ranks fifth globally for DM prevalence, with 19.5 million cases (10.8%) reported in 2021. Dietary fiber intake plays a crucial role in glycemic regulation through mechanisms involving delayed gastric emptying and enhanced insulin sensitivity. However, evidence regarding the association between daily fiber consumption and glycemic control in type 2 DM patients without complications remains inconclusive, particularly in primary care settings. Objective: This study aimed to examine the association between daily fiber intake and random blood glucose (RBG) levels among patients with uncomplicated type 2 diabetes mellitus in Banda Sakti District, Lhokseumawe City. Methods: A cross-sectional analytical study was conducted at Banda Sakti and Mon Geudong Primary Health Centers from May 2023 to February 2024. A total of 51 participants with uncomplicated type 2 DM were recruited using total sampling. Daily fiber intake was assessed through 24-hour food recall and analyzed using Nutrisurvey software, while RBG levels were measured using a standardized glucometer (ISO 15197:2013). Data analysis employed univariate descriptive statistics and bivariate analysis using Fisher's Exact test, with statistical significance set at p<0.05. Results: The majority of respondents were female (66.7%, n=34), elderly (>60 years, 51.0%, n=26), with higher education levels (60.8%, n=31), and normal body mass index (54.9%, n=28). Suboptimal daily fiber intake (<20 g/day) was observed in 80.4% (n=41) of participants, and poor RBG control (>200 mg/dL) was found in 68.6% (n=35). Although a trend indicated better RBG levels among those with adequate fiber intake (60% had good RBG vs. 24.4% in the insufficient group), statistical analysis revealed no significant association (p=0.054, Fisher's Exact test). Conclusion: Despite the absence of a statistically significant correlation between daily fiber intake and random blood glucose levels in this study, the observed trend suggests the potential clinical relevance of adequate fiber consumption for glycemic management. Future studies with larger sample sizes, prospective designs, and consideration of confounding factors including medication adherence, physical activity, and comprehensive dietary patterns are warranted to further elucidate this relationship.